A general equilibrium analysis of the effect of macroeconomic adjustment of poverty in Africa - Dorosh, Paul A.; Sahn, David E. (Elsevier, 2000)
Using CGE models for four countries (Cameroon, The Gambia, Madagascar, and Niger), this paper examines the consequences of macropolicy reform on real incomes of poor households in sub-Saharan Africa The simulations suggest that, compared to alternative policy options, trade and exchange rate liberalization tends to benefit poor households in both rural and urban areas-as rents on foreign exchange are eliminated, demand for labor increases, and returns to tradable agriculture rise. The small magnitudes of the gains in average real incomes of poor household groups modeled suggest that macropolicy reform alone will not be sufficient in the short run to significantly reduce poverty in Africa." -- Authors' Abstract